Terror in the Mind of God The Global rise of religious violence - Juergensmeyer, Mark (Berkeley University of California Press, 2003)
Examines such incidents as the 1993 World Trade Center bombing, the Tokyo subway nerve gas attack, and the killing of abortion clinic doctors in the U.S. to explore the reasons behind acts of violence committed for religious causes.
Keywords: Violence -- Religious aspects. Violence -- Aspect religieux. Gewalt Religion